Investigation of plasma concentrations of IL-6 and IL-10 in short and long-term opioid users with non-cancer pain - Zin, Che Suraya; Mizher, Hussam A.; Mohamed, A.; Tan, Teik Hin; Izat, Munira (2018)
Introduction: The pro-inflammatory cytokine (interleukin-6 (IL-6)) and the anti-inflammatory cytokine (interleukin-10 (IL-10)), are believed to play a key role in the pathophysiology of the chronic pain. Recent research highlights the potential role of these cytokines in modulating the analgesic effect of opioid in long-term users which may contribute to opioid tolerance. Aims of investigation: This study examined the plasma concentration levels of pro-inflammatory cytokine, IL-6, and anti-inflammatory cytokine, IL-10, in short, and long-term opioid users treated for non-cancer pain. Methods: This preliminary study was conducted at pain clinics in two tertiary hospitals in Malaysia from March 2016 to February 2017. Patients were recruited if they were prescribed with any of the five available opioids (morphine, oxycodone, fentanyl, buprenorphine, and dihydrocodeine) for non-cancer pain. Patients were categorized into short-term opioid users (who used opioid for < 90 days per year) and long-term opioid users (who used opioid > 90 days per year). For long-term opioid users, they were further categorized into adherent and non-adherent based on medication possession ratio (MPR). MPR is a measure of adherence indicating the ratio of the medication days’ supply over a specific period of time. Patients with MPR ≥ 80% were included in the adherent group and MPR ≤ 80% in the non-adherent group. MPR is not applicable for short-term opioid users because it needs at least 3 prescriptions to be calculated, and most of the short-term opioid users were prescribed with less than 3 opioid prescriptions. For all patients included in this study, a 10 ml venous blood samples were collected during their scheduled visit to the clinic, and their plasma concentrations of IL-6 and IL-10 were measured using multiplex ELISA assays. The plasma concentrations of IL-6 and IL-10 were compared between long and short-term users and were correlated within each group. The same analyses were also conducted between the adherent and the non-adherent groups. All analyses were performed using SPSS version 20. Results: Thirty-eight patients were recruited into the study. Of these, 21% (n=8) were short-term opioid users and 79% (n=30) were long-term opioid users. Short-term opioid users have higher levels of IL-6 and IL10 concentration than that of long-term opioid users but both cytokine levels did not reach a statistical significance. Among long-term opioid users, the plasma concentration of both IL-6, and IL-10 were lower in the adherent group than in the non-adherent without reaching a statistical significance. Within the same adherent and non-adherent groups, the plasma concentration level of IL-6 was significantly higher than IL-10 in both groups. However, interestingly, the adherent group showed a strong correlation between IL-6 and IL-10 with r-squared of 0.91. The same correlation was also seen in the short-term opioid users (r-squared 0.80) and non-adherent group (r-squared 0.69). Conclusions: Duration of opioid use either short term or long term and adherence to opioid therapy were found to affect the plasma concentrations of IL-6 and IL-10 in patients with non-cancer pain. High plasma concentration levels of IL-6 and IL-10 were observed in short-term opioid users compared with long-term opioid users. The adherent long-term opioid users were found to have lower plasma concentrations levels of IL-6 and IL-10 than the non-adherent users. Future research is warranted to evaluate whether the difference in the plasma concentrations of IL-6 and IL-10 is associated with the occurrence of opioid tolerance.